Research in social movements, conflicts and change. Vol. 31 - Coy, Patrick G. (Research in social movements, conflicts and change., 2010)
This latest volume in the Research in Social Movements, Conflicts and Change series contains three sections of data-driven articles that address topics central to scholarship on social movements and conflict resolution. Section One contains two papers on the Palestinian-Israeli conflict, one focused on the Arab Israeli Land Day campaign and its implications for political process theory, while the other analyzes the emotional landscape of the long-running Women in Black vigils. Section Two contains four papers linked by their treatment of tactical and strategic issues associated with gender-based and gay and lesbian social movements, organizations, and their campaigns and activities. The two articles in Section Three treat themes associated with the complex intersection of identity formation and mobilization. As has long been the RSMCC series tradition, Volume 31 showcases top-level, original, and multi-method research on a variety of movements, organizations and conflicts in ways that contribute to theory-building.